2003
DOI: 10.1177/0261927x03022002004
|View full text |Cite
|
Sign up to set email alerts
|

Language, Gender Salience, and Social Influence

Abstract: Reductionist explanations for gender differences in language use continue to occupy much research attention. However, such approaches cannot explain when or why people might change their gender-marked language use. This article reviews and critiques several of these approaches and tests an alternative from the perspective of self-categorization theory. Male-female dyads (N = 42) discussed a gender-neutral controversial issue under conditions of low or high gender salience. When a shared student identity was sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 28 publications
2
99
2
1
Order By: Relevance
“…For example, Carli (1990) found that tentative speakers, regardless of their gender, received lower ratings on power, competence, and intelligence than direct individuals. On the other hand, tentative language can be beneficial for communicators: Reid et al (2003), for example, showed that under certain conditions tentative women were more persuasive with men than direct women were, even though men judged tentative women less favorably. Tentative language is particularly significant in computer-mediated communication (CMC), such as e-mail, wherein social cues are limited (Dubrovsky, Kiesler, & Sethna, 1991).…”
mentioning
confidence: 99%
“…For example, Carli (1990) found that tentative speakers, regardless of their gender, received lower ratings on power, competence, and intelligence than direct individuals. On the other hand, tentative language can be beneficial for communicators: Reid et al (2003), for example, showed that under certain conditions tentative women were more persuasive with men than direct women were, even though men judged tentative women less favorably. Tentative language is particularly significant in computer-mediated communication (CMC), such as e-mail, wherein social cues are limited (Dubrovsky, Kiesler, & Sethna, 1991).…”
mentioning
confidence: 99%
“…Instead of witnesses speaking in a typically female or male, rich or poor, or educated or uneducated style, they might use a common courtroom style. This was observed by Reid et al (2003) who found that women used more ten tative language in discussions where gender had been made salient compared to low gender salience discussions where instead student identity was salient. In the latter situations, men and women used about the same amount of tentative language.…”
Section: Support For the Main Hypotheses?mentioning
confidence: 80%
“…In these contexts, the institutional roles, in this case the role of witness, are so powerful and standardised and include so many requirements and expectations that they overrule gender roles. Therefore, following Reid et al (2003), these contexts do not produce any gender-based language differences or at least very subtle ones requir ing a large material to detect them. An infl uential factor therefore in stead becomes whether a witness has previous experience from testifying or otherwise is familiar with the courtroom context, i.e.…”
Section: Resultsmentioning
confidence: 96%
“…Examinations of apologies-which some have construed as an indicator of politeness and a feminine language style (Herring, 1993;Lakoff, 1975)-have yielded a similarly diverse array of differences and similarities between men and women (O'Neill & Colley, 2006;Savicki, Lingenfelter, Kelley, 1996;Tannen, 1990;Thomson, 2006). Tentative language signals uncertainty, is typically associated with women (Herring, 1993;Lakoff, 1975), and like apologies and references to emotion is contextually dependent (Brouwer, Gerritsen, & De Haan, 1979;Carli, 1990;Palomares, 2008Palomares, , 2009S. A. Reid, Keerie, & Palomares, 2003;Tannen, 1990).…”
Section: Introductionmentioning
confidence: 99%